Multiculturalism in the world system: towards a social justice model of inter/multicultural education. (1st January 2020) - Torres, Carlos Alberto; Tarozzi, Massimiliano
ABSTRACT: Multiculturalism burst in Asia with the winds of globalisation. Fuelled by immigration, cultural hybridity and normative regimes from multilateral and bilateral organisations, multiculturalism is a new challenge for Asian economies, their politics of culture and their higher education institutions. Moreover, although heavily implemented from the start of the last century in the United States and in Europe to some extent, multiculturalism and multicultural education signify a premise in constructing models of cosmopolitan democracies and what has been known as 'global citizenship education'. Drawing from the more mature experiences of the European Union (EU) and the United States in this field, this article traces the theoretical contours of and debates within multiculturalism. The article also focuses on the learning experience across borders, which is well represented in international comparative education studies. It probes the occurrence of any crisis in the field of multiculturalism in the United States and EU. Lessons learned from a comparison of the U.S. and EU experiences may be instructive to the Asian economies and cultures that are dealing with multiculturalism as a new force in the world system.